Literature Survey On Fingerprint Recognition Using Level 3 Feature Extraction Method (International Journal of Engineering and Computer Science, 2014)
To design Level 3 fingerprint feature extraction method and match using SIFT algorithm. First of all fingerprint of good quality are acquired by using optical scanner. Normalization of image is done using Gaussian blurring and sliding window contrast adjustment. Pores are extracted and estimated. These estimated pores, are used to match from template database to stored database using SIFT algorithm. Scale Invariant Features Transform (SIFT) is an algorithm in computer vision to detect and describe local features in images. The features are invariant to image scaling and rotation. They are well localized in both the spatial and frequency domains. The features are highly distinctive, which allows a single feature to be correctly matched with high probability against a large database of features, providing a basis for object and scene recognition.